Representasi Pola Komunikasi Keluarga dalam Film Dua Garis Biru - Ibnu Ibrahim (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Communication within the family is an important foundation in shaping children's character and mindset, especially when facing conflicts or sensitive issues such as teenage pregnancy. The film Dua Garis Biru by Gina S. Noer realistically depicts the dynamics of communication between family members when faced with surprising and stressful situations. This study aims to examine how family communication patterns are represented in the film, and how these communication messages reflect the social conditions of Indonesian society. This study uses a qualitative method with a content analysis approach, especially in scenes showing interactions between the main characters and their respective parents. The results of the study show that this film represents a family communication pattern that is authoritative, closed, but slowly develops into a more open and empathetic one along with the ongoing conflict. The film Dua Garis Biru not only presents teenage conflicts, but also reflects the importance of openness and emotional support in family communication. This representation can be a reflection for parents and teenagers in building healthy and solution-oriented communication within the family.